Nilai-Nilai Tradisi Pingkama'a-Ma'a pada Masyarakat Kelurahan Wali Kecamatan Binongko Kabupaten Wakatobi - Nurtikawati Nurtikawati; Santika Santika; La Niampe (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
Many values are implied in the pingkama'a-ma' tradition but many people do not understand it so this study aims to determine the process of implementing the pingkama'a-ma'a tradition, the values in the pingkama'a-ma'a tradition, as well as changes in the pingkama'a-ma'a tradition. pingkama'a-ma'a tradition process. This study uses qualitative research methods, data collection is carried out by observation techniques, the second is interviews with sources or informants, and the third is documentation. The tools used in the field research are special notes and recording devices. Data analysis techniques take place continuously at each stage of the research until it is complete. The process of implementing the pingkama'a-ma'a tradition is carried out after completing the Eid al-Fitr prayer or Eid al-Adha prayer. When the pingkama'a-ma'a tradition takes place, there are no restrictions on anyone who wants to join in on the fun. The benefits of the pingkama'a'a-ma'a tradition are as entertainment for the community, as a place of friendship between fellow humans and as a place to find a mate for young people.